2018
DOI: 10.3390/toxins10120487
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Toxicity of Solasonine and Its Effects on cyp450 Family Gene Expression in the Livers of Male Mice from Four Strains

Abstract: Solasonine was reported to inhibit tumour cell growth in several different models. The in vivo toxicity of solasonine, the effects of genetic background on its toxicity, and its possible roles in regulating the expression of cyp450 family genes were still unclear and required characterisation. Here, Horn’s assays were performed on male mice from four different strains, and the expression of cyp450 family genes in their livers was examined by RT-PCR and ELISA. Mice treated by intraperitoneal injection with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…We also found that protein and mRNA levels of CHST4 were low in the liver in BALB/c mice, while high mRNA levels and low protein levels were observed in the pancreas. In contrast, the mRNA levels of CHST4 were high in the pancreas and liver in C57BL/6 mice (12), which may be related to the different strains of mice (45). The difference in protein and mRNA levels may be due to translation or posttranslational modifications (46) of CHST4, although this has not yet been verified.…”
Section: Discussionmentioning
confidence: 91%
“…We also found that protein and mRNA levels of CHST4 were low in the liver in BALB/c mice, while high mRNA levels and low protein levels were observed in the pancreas. In contrast, the mRNA levels of CHST4 were high in the pancreas and liver in C57BL/6 mice (12), which may be related to the different strains of mice (45). The difference in protein and mRNA levels may be due to translation or posttranslational modifications (46) of CHST4, although this has not yet been verified.…”
Section: Discussionmentioning
confidence: 91%
“…The extract possesses medicinal properties [ 14 ] including anticancerous ones [ 15 ]. Solasonine and solamargine also have anticancer properties proved in many studies [ 16 , 17 , 18 ], having low toxicity [ 19 , 20 ]. Additionally, the persistence in the environment of glycoalkaloids is short [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primer sequences and PCR ampli cation reactions were as according to the literature (Yan, Zeng et al 2014). The internal reference gene of the experiment was GAPDH (Zhong, Li et al 2018). The primer sequences and reaction systems are shown in Tables 1 and 2.…”
Section: Rna-isolation and Qpcrmentioning
confidence: 99%